Peran Pengawasan dan Budaya Organisasi terhadap Efektivitas Kerja Pegawai Sekolah Tinggi Ilmu Kesehatan (STIKES) Al-Ma’arif Baturaja - Yulita Eka Fitri (JEM Jurnal Ekonomi dan Manajemen, 2019)
Indonesia has a problem of poverty and unemployment. poverty in Indonesia can be seen from three approaches namely natural poverty structural poverty, and regional disparity. The problem of unemployment is more driven by low employment opportunities and opportunities for the workforce in rural areas. Efforts to overcome this must use an organizational culture approach that has a supervisory dimension This study aims to examine the relationship between supervision and organizational culture on employee work effectiveness, a study was conducted on 33 employees at the Al-Ma'arif Baturaja Ogan Komering Ulu School of Health. by using a regression method. The results of the study confirm that supervision and organizational culture affect the work effectiveness of employees at the health science high school (STIKES) Al-Ma'arif Baturaja Ogan Komering Ulu